Blogging for professional development: a case study of pre-service teachers in an integrative blended-learning course - Luzzatto, Efrat; Fono, Dafna; Biberman-Shalev, Liat (Frontiers in Education, 2025)
The increasing demand for innovative teaching methods in teacher education has led to the development of integrative courses that utilize blended learning and digital tools such as blogs to enrich the preparation of pre-service teachers in special education. This study examines how personal blogging, as part of a blended-learning integrative course, supports the professional development of 61 pre-service special-education teachers. Conducting an online blog was a requirement of an integrative blended-learning course titled “Students with Learning Disabilities.” Through thematic analysis of 268 blog entries, this study reveals a range of benefits of blogging, encompassing cognitive, emotional, and reflective dimensions. Six main themes emerged following this analysis, including: (1) reconstructing and documenting course content; (2) addressing unique teaching practices; (3) reflecting on the unique features of the integrative course; (4) freely expressing significant emotions; (5) deepening the understanding of the teacher's role; and (6) challenges of blended learning in the context of the integrative course. The blogs served as an effective tool for documenting lessons, processing knowledge, and engaging in critical reflection, while also facilitating emotional expression and professional insights. The findings underscore the blog's significance as a reflective instrument that bridges face-to-face and online learning environments, supporting the professional growth of pre-service teachers. This research contributes to the growing discourse on innovative teacher training, elucidating both the benefits and challenges of including personal blogs in integrative blended courses. The study's outcomes offer valuable insights for teacher educators and curriculum designers seeking to enhance pre-service teacher preparation through digital reflective practices.